2017
DOI: 10.4174/astr.2017.92.3.149
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic resection of retroperitoneal benign neurilemmoma

Abstract: PurposeThe aim of this study was to verify that laparoscopic resection for treating retroperitoneal benign neurilemmoma (NL) is expected to be favorable for complete resection of tumor with technical feasibility and safety.MethodsWe retrospectively analyzed 47 operations for retroperitoneal neurogenic tumor at Yonsei University College of Medicine, Severance Hospital and Gangnam Severance Hospital between January 2005 and September 2015. After excluding 21 patients, the remaining 26 were divided into 2 groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
0
10
0
10
Order By: Relevance
“…In recent years, endoscopic or robotic minimally invasive surgery is also being employed for the management of retroperitoneal schwannomas, with an acceptable rate of surgical complications [1719]. Ji et al reported complication rates of 12.5% with laparoscopic resection of retroperitoneal schwannomas [18], while Liu et al reported complication rates of 12% with robotic resections of benign retroperitoneal tumors, including schwannomas [19].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, endoscopic or robotic minimally invasive surgery is also being employed for the management of retroperitoneal schwannomas, with an acceptable rate of surgical complications [1719]. Ji et al reported complication rates of 12.5% with laparoscopic resection of retroperitoneal schwannomas [18], while Liu et al reported complication rates of 12% with robotic resections of benign retroperitoneal tumors, including schwannomas [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fue Masson quien describió su origen en las vainas nerviosas (Schwannomas) (1,2,6) . Los Tumores retroperitoneales, poco frecuentes, representan 1% de todos los tumores (4) y los schwannomas o neurilemomas representan entre el 1 al 10% de ellos (7)(8)(9)(10)(11)(12)(13)(14)(15) . A su vez los schwannomas son más frecuentes en cabeza, cuello y miembros (9)(10)(11)(12)14) .…”
Section: Discussionunclassified
“…The etiology of schwannomas remain unclear. [ 6 8 ] Schwannoma can affect any nerve trunk or any organ, but it occurs predominantly in the upper extremities. Less than 9% of schwannomas found in the mediastinum, but this tumor is the most common neurogenic tumor of the lower posterior mediastinum.…”
Section: Discussionmentioning
confidence: 99%